The Opinion of Slovenian Students about YouTube as a Digital Education Platform - Romih, Dejan; Malc, Domen (Digital Platforms: Legal And Economic Challenges, 2024)
In this paper, we analyse the opinion of Slovenian students about YouTube as a digital education platform. Based on a survey conducted in November 2023 among 299 undergraduate and postgraduate students, we found that respondents generally have a very positive opinion of YouTube as a digital education platform, which we expected given the fact that YouTube is very popular among Generation Z members. However, they do have concerns about the reality and accuracy of the educational content, as well as its comprehensibility. These findings are important because they give us an insight into the state of play in this area.